Identifikasi bakteri patogen pada ikan Nila (Oreochromis niloticus) di lokasi budidaya ikan air tawar Kabupaten Kepulauan Sangihe - Manurung, Usy N.; Susantie, Darna (e-Journal BUDIDAYA PERAIRAN, 2017)
This research aimed to identify pathogenic bacteria that infected nile tilapia (Oreochromis niloticus) cultivated at five Districts in Tahuna Regency including Tamako, Kecamatan, Tabukan Tengah, Tabukan Utara,  Manganitu and Tahuna Districts, and to analyze water quality (temperature and pH).  The research was  conducted from July to August 2017.  Isolation and identification of bacteria was performed at  the Test Laboratory, Station of Fish Guarantee, Quality Control and Fisheries Product Safety Grade II, Tahuna. Target organ examined was kidney.  The bacteria was grown on TSA and then isolated. The bacteria was identify by gram stain, motility, aerobic, catalase, oxidase, O/F, glucose and Rimler shots for Aeromonas hydrophila. The bacteria was then identified using Manual for the Identification of Medical Bacteria.   From the 30 samples identified, it was found seven pathogenic bacteria infected fish namely A. hydrophila observed at 11 fish (36.6%), Corynebacterium sp. observed at 6 individuals or 20 %, Enterobacteria sp. obtained at 5 fish or 16,6 %, Listeria sp.  at 2 fish or 6,6 %, Pseudomonas sp. at 1 fish or 3,3 %, Plesiomonas sp. at 1 fish or 3,3 % and Kurtiha sp. at 1 fish.  Water quality parameters at all five districts ranged between 25 and 28° C while pH ranging from  6- 7 and suitable based on the PP N9. 42 Tahun 2001.Keywords:  pathogenic bacteria, aquaculture, Oreochromis niloticus